Economic impacts of climate change and climate change adaptation strategies in Vanuatu and Timor-Leste. (May 2016) - Rosegrant, Mark W.; Dey, Madan Mohan; Valmonte-Santos, Rowena; Chen, Oai Li
Abstract: The fisheries sectors in Vanuatu and Timor-Leste are important sources of food and income. Similar to other developing countries and those in the Pacific, they are vulnerable to the impacts of climate change more so because of their geographic location, socioeconomic conditions and political instability. Nonetheless, there are approaches to alleviate the damaging effects of climate change in the region's fisheries sector. Using economic modeling, this paper estimates the economic costs of potential climate change adaptation strategies for the fisheries sector in Vanuatu and Timor-Leste through assessment of alternative future scenarios. Strategies include aquaculture development, natural resource management through establishment and/or expansion of marine protected areas, and deployment of low-cost inshore fish aggregating devices. Modeling results demonstrate that the above innovations will enable the two countries to significantly improve coastal and freshwater fish production in the medium-term (2035) and long-term (2050). Fish consumption is projected to grow due to population and income improvements; yet considerable increases in production will augment demand. Furthermore, national-level gains are projected from these adaptation strategies through fish exports. Improved production under climate change will require significant investments from the national governments of Vanuatu and Timor-Leste and/or private sectors. Highlights: Analyzed economic impact of adaptation strategies in Vanuatu and Timor-Leste. Strategies: aquaculture, natural resource management, and inshore fish aggregating devices. Positive impact of strategies, but current scales of adaptation are too small. Need aggressive, but judicious, increases in investments in adaptation strategies. Essential to tailor these strategies and policies to conditions in various locations.